An Appraisal of A Successful Integrated Hill Farming System - Pande, Kamal K.; Singh, N. K.; A., Vijayavinashilingam N.; Joshi, Harish (Indian Farming, 2015)
The successful establishment and running of integrated hill farming system having nine compatible agricultural and allied components proves a lot. This appraisal of integrated farming system opens new avenues to self dependency and prosperity of hill farmers. Efforts from all concerned departments and agencies should be made to demonstrate and develop such integrated hill farming systems for even small lands for the betterment of hill farmers and conservation of natural resources.